Phthalates exposure indicators determined by urinary phthalate metabolites in healthy non-obese Czech adults: FANTOM study - Müllerová, Dana; Bouchalová, Vendula; Matějková, Dagmar; Kovářová, Kateřina; Svačina, Štěpán; Vrbík, Karel; Pavloušková, Jana; Dvořáková, Jana; Müller, Luděk (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2016)
It is assumed that human exposure to phthalates may be associated with adverse health effects. The indicators of urinary phthalate metabolite concentrations in healthy adults are limited. In this study, the phthalate metabolites concentrations were detected from 24-h urine collection in non-obese Czech adults (n = 201). Each participant filled in an 80-item questionnaire (FANTOM-SQ 2013) regarding the outdoor and indoor sources of phthalates, the use of personal care products and food intake sources. The concentrations of 15 phthalates metabolites were analysed following enzymatic cleavage of the glucuronide using ultra-high-performance liquid chromatography-electrospray ionisation tandem mass spectrometry (UHPLC-ESI-MS/MS). The indicators of chronic or acute exposure phthalate-containing materials were identified. It is shown that higher fruit consumption was positively and significantly associated with a higher level of total 15 urinary phthalates biomarkers (p < 0.001). Regular meat consumption showed a negative significant association with total 15 phthalates metabolites (p < 0.01). The use of personal care products was significantly and positively correlated with monoethyl phthalate urine concentrations (p < 0.05). The analysis of the dietary behaviour and personal care products use in the Czech non-obese population showed it to be a predictable tool in the level of phthalates exposure when high fruit consumption and personal care products use are linked to higher phthalate metabolite contents in the urine. However, this topic deserves more research.
Keywords: Phthalic Acids; exposure indicators; normal body weight; Healthy Volunteers; kyseliny ftalové; Česká republika; Fruit; maso; ovoce; Chromatography, High Pressure Liquid; Czech Republic; vysokoúčinná kapalinová chromatografie; kontaminace potravin; Humans; Urinary phthalates biomarkers; Tandem Mass Spectrometry; biologické markery; Food Contamination; Meat; tandemová hmotnostní spektrometrie; Biomarkers; consumer practices; lidé; zdraví dobrovolníci pro lékařské studie